Pemaksaan Kedewasaan Karena Perkawinan: Antara Fiksi Hukum dan Perlindungan Anak: (Studi Perbandingan di Malaysia, Filipina dan Belanda) - Suyikati suyikati (CV Rewang Rencang, 2025)
Child marriage is a form of coercion into adulthood that has a serious impact on the mental health, social, and legal development of children, especially women. Children who marry early often experience stress, depression, and anxiety disorders due to the pressure of adult roles that they are not ready to take on psychologically and socially. In addition, this marriage increases the risk of domestic violence, school dropout, and being trapped in an intergenerational cycle of poverty. In a legal context, a child who marries is automatically considered an adult and legally capable, even if emotionally and mentally unprepared, making it vulnerable to exploitation and legal harm. This study uses a normative method with a comparative approach to law, especially against the practice in the Netherlands and the Philippines, which have established an absolute ban on child marriage without a gap in legal dispensation. In contrast, Indonesia and Malaysia still provide dispensation spaces that are often used on the basis of culture or pregnancy outside of marriage. This discussion shows the importance of reforming national laws in favor of the protection of children as a whole, through the elimination of legal loopholes dispensation and strengthening social-based approaches to education and rehabilitation. Synergy between regulation, law enforcement, and changes in social norms is needed to end the practice of child marriage as a whole.